The Thorpex polar low analysed with AROME-Arctic - Stoll, Patrick J.; Valkonen, Teresa M.; Graversen, Rune G.; Noer, Gunnar (2019)
Presentation at the European Geoscience Union General Assembly conference, Vienna, Austria, 07.04.19 - 12.04.19. ( https://www.egu2019.eu/.